PBC@cellulose-filter paper separator design with efficient ion transport properties toward stabilized zinc-ion battery. (20th October 2022) - Li, Linbo; Peng, Jiaxin; Jia, Xuefeng; Zhu, Xiaojie; Meng, Bicheng; Yang, Kai; Chu, Dewei; Yang, Naixing; Yu, Juan
Abstract: The uneven pore structure and sluggish transport kinetics of the separator will accelerate the growth of dendrites and directly deteriorate the performance of zinc metal battery. Herein, we present a simple and unique interface engineering strategy to anchor persimmon branch carbon (PBC) material onto a cellulose-filter (CF) paper separator to address these issues. The novel PBC material demonstrates a hierarchical pore structure, uniform distribution of carbon dots, and rich N, and O functional groups, and an efficient ion transport modulator PBC@CF separator is designed to serve the dual function of promoting ions transfer and suppressing dendrite growth. Owing to the anchoring of PBC on CF and uniform filling of the surface interspace, the PBC modified separator not only greatly facilitates Zn 2+ transport between the fiber-electrolyte interface, but also evenly redistributes the ion transport on the anode interface. As a result, highly reversible Zn plating/stripping is achieved in the symmetric Zn-Zn cell with the PBC@CF separator. Meanwhile, the modified Zn-LiFePO4 dual ion full battery can retain a specific capacity of 109.4 mAh g −1 after 200 cycles at 1 C with an excellent capacity retention of 86 %. The unique PBC material and facile separator engineering provide a new perspective to designing advanced separators for high-performance aqueous Zn dual ion full battery.